Deixis in Song Lyrics: A Pragmatic Analysis of Wiz Khalifa’s ‘See You Again’ and ‘Roll Up’ - Yusuf, Muhammad; Afriana (ENGLISH JOURNAL OF INDRAGIRI, 2026)
This study analyses the types of deixis found in Wiz Khalifa’s selected songs through a pragmatic lens. Deixis, the study of how language elements refer to contextual features such as participants' roles and their social and temporal settings, is examined based on Brown and Levinson’s (1978) theory. The research employs a qualitative approach, involving the listening to and transcribing of the lyrics, followed by categorizing deixis expressions. A total of 343 occurrences of deixis were identified, with person deixis (262 instances) being the most frequent, followed by spatial deixis (15), temporal deixis (59), and discourse deixis (7). This finding shows that person deixis dominates in expressive and narrative lyrics of both songs because it directly involves the speaker and the addressee, making the message more personal and relatable to listeners.